(untitled) (Research, Society and Development, 2025)
The success of endodontic treatment depends on the quality of cleaning and obturation of the Root Canal System (RCS), which are challenged by morphological variations such as isthmuses, polar areas, and accessory canals. Failure to locate all root canals can result in persistent infections or reinfections, significantly contributing to treatment failure. Upper premolars with three roots represent a rare anatomical variation, requiring a meticulous approach to achieve therapeutic success. This study aims to report the endodontic treatment of a left upper premolar with three roots and three canals, with independent foraminal exits. A 38-year-old male, Caucasian patient, was referred for endodontic treatment of the left second upper premolar. Upon clinical examination, tooth 25 showed an exaggerated response to the vitality test, and the radiographic examination revealed an atypical anatomy with three roots and three canals. The first session was dedicated to locating and performing complete chemical-mechanical preparation of the three canals using stainless steel files (C-pilot®), rotary instruments (Bondent Platinum®). An intracanal medication containing calcium hydroxide combined with 2% chlorhexidine gel was placed for 21 days. In the second visit, the root canal system was obturated with Endofill® sealer. The endodontic treatment of teeth with complex anatomy, such as tooth 25 with three independent canals, emphasizes the need for meticulous planning and the use of advanced technologies for clinical success.